ANALISIS YURIDIS PEMBELAAN TERPAKSA DIRI SENDIRI BERDASARKAN PASAL 49 KITAB UNDANG-UNDANG HUKUM PIDANA - Marrio Nicholas; Petrus Irwan Panjaitan; Radisman Saragih (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The definition of forced defense when viewed in terms of language, forced defense or noodweer consists of the words nood and "weer". Nood which means an emergency or in an unexpected (difficult) situation, which requires immediate response in a forced situation. Weer means defense which means the act of defending, helping, releasing from danger. Forced Defense Exceeding Limits (noodweer exces) has two conditions to be able to declare someone carrying out forced defenses that are exceeding limits. First, there must be a situation that gives rise to forced defense as discussed above (Article 49 paragraph (1) of the Criminal Code). Second, there must be great mental turmoil as a result of the attack causing a forced defense that goes too far. Based on the formulation of Article 49 paragraph (2) of the Criminal Code The purpose of this research is to find out and discuss protection, the rights of victims who are subject to criminal sanctions by judges and an analysis of the decisions given by judges in the case study case Number 1/Pid.Sus-Anak/2020/PN kpn. The writing of this law uses a normative juridical research method, the type of data used is secondary data, the approach method used is a statutory approach, and data analysis uses qualitative analysis to determine protection for victims of wiretapping.